Predictions of Dust Continuum Emission from a Potential Circumplanetary Disk: A Case Study of the Planet Candidate AB Aurigae b - Yuhito Shibaike; Jun Hashimoto; Ruobing Dong; Christoph Mordasini; Misato Fukagawa; Takayuki Muto (The Astrophysical Journal)
Gas-accreting planets embedded in protoplanetary disks are expected to show dust thermal emission from their circumplanetary disks (CPDs). However, a recently reported gas-accreting planet candidate, AB Aurigae b, has not been detected in (sub)millimeter continuum observations. We calculate the evolution of dust in the potential CPD of AB Aurigae b and predict its thermal emission at 1.3 mm wavelength as a case study, where the obtained features may also be applied to other gas-accreting planets. We find that the expected flux density from the CPD is lower than the 3 σ level of the previous continuum observation by the Atacama Large Millimeter/submillimeter Array with broad ranges of parameters, consistent with a nondetection. However, the expected planet mass and gas accretion rate are higher if the reduction of the observed near-infrared continuum and H α line emission due to the extinction by small grains is considered, resulting in higher flux density of the dust emission from the CPD at (sub)millimeter wavelengths. We find that the corrected predictions of the dust emission are stronger than the 3 σ level of the previous observation with the typical dust-to-gas mass ratio of the inflow to the CPD. This result suggests that the dust supply to the vicinity of AB Aurigae b is small if the planet candidate is not the scattered light of the star but is a planet and has a CPD. Future continuum observations at shorter wavelengths are required to obtain more robust clues to the question of whether the candidate is a planet or not.